A New Jarratt-Type Fourth-Order Method for Solving System of Nonlinear Equations and Applications. (25th March 2015) - Junjua, Moin-ud-Din; Akram, Saima; Yasmin, Nusrat; Zafar, Fiza
Abstract : Solving systems of nonlinear equations plays a major role in engineering problems. We present a new family of optimal fourth-order Jarratt-type methods for solving nonlinear equations and extend these methods to solve system of nonlinear equations. Convergence analysis is given for both cases to show that the order of the new methods is four. Cost of computations, numerical tests, and basins of attraction are presented which illustrate the new methods as better alternates to previous methods. We also give an application of the proposed methods to well-known Burger's equation.